Potential Use of Dragon Fruit and Taro leaves as Functional Food: A Review (European Journal of Engineering Science and Technology, 2018)
Fruits and vegetables are important constituents of our diet which provide significant quantities of nutrients especially vitamins, minerals, and fiber. Daily consumption of fruits and vegetables reduce the risk of cancer, heart disease, premature aging, and stress. ‘Fruit and vegetable-based dried powders? are one of the best sources of vitamins, minerals, fibers and valuable bioactive compounds which are essential for human health. The health benefits associated with fruits and vegetables on a daily basis are related to the ingestion of bioactive components. Taking into consideration of associated health benefits on present work deals with a new development of functional food powder prepared by using dragon fruit and taro leaves because dragon fruit and taro leaves contain vitamin C and B, and phytochemicals which are essential to maintain good health. These two possess various nutraceutical activities such as antioxidant, anticancer, antifungal, curing of various diseases like cancer, cardiovascular disease, coronary heart disease, etc. The future development of functional foods will require contributions from basic and applied scientists in academia, government, and industry.